The Ruling on Guardianship in the Validity of Marriage Contracts, A Comparative Study between the Maliki School and the Libyan Marriage and Divorce Law - Mohamed Ben Faid; Recep Ozdirek (Zenodo, 2025)
ABSTRACT  Jurists differed in their understanding of the texts of the Qur’an and Sunnah, and as a result, schools of jurisprudence emerged, including the four schools, and the people of each country adhered to one school. Then came the movement to codify Sharia, so the formula of laws was formulated and branched out according to each specialty and according to articles, including the Personal Status Law, or what is known as the Marriage Law, The subject of our paper was to shed light on the role of guardianship in the validity of the marriage contract according to the Maliki jurisprudence applicable in the State of Libya and the Libyan Marriage and Divorce Provisions Law, or what is known as the Libyan Personal Status Law.